Flavonoids from Tetracera indica Merr. induce adipogenesis and exert glucose uptake activities in 3T3-L1 adipocyte cells - Hasan, Md. Mahmudul; Ahmed, Qamar Uddin; Mat Soad, Siti Zaiton; Latip, Jalifah; Taher, Muhammad; Tengku Zakaria, Tengku Muhamad Faris Syafiq; Sarian, Murni Nazira; Alhassan, Alhassan Muhammad; Zakaria, Zainul Amiruddin (BioMed Central, 2017)
Background: Tetracera indica Merr. (Family: Dilleniaceae), known to the Malay as ‘Mempelas paya’, is one of the medicinal plants used in the treatment of diabetes in Malaysia. However, no proper scientific study has been carried out to verify the traditional claim of T. indica as an antidiabetic agent. Hence, the aims of the present study were to determine the in vitro antidiabetic potential of the T. indica stems ethanol extract, subfractions and isolated compounds. Methods: The ethanol extract and its subfractions, and isolated compounds from T. indica stems were subjected to cytotoxicity test using MTT viability assay on 3T3-L1 pre-adipocytes. Then, the test groups were subjected to the in vitro antidiabetic investigation using 3T3-L1 pre-adipocytes and differentiated adipocytes to determine the insulinlike and insulin sensitizing activities. Rosiglitazone was used as a standard antidiabetic agent. All compounds were also subjected to fluorescence glucose (2-NBDG) uptake test on differentiated adipocytes. Test solutions were introduced to the cells in different safe concentrations as well as in different adipogenic cocktails, which were modified by the addition of compounds to be investigated and in the presence or absence of insulin. Isolation of bioactive compounds from the most effective subfraction (ethyl acetate) was performed through repeated silica gel and sephadex LH-20 column chromatographies and their structures were elucidated through 1 H–and 13C–NMR spectroscopy. Results: Four monoflavonoids, namely, wogonin, norwogonin, quercetin and techtochrysin were isolated from the T. indica stems ethanol extract. Wogonin, norwogonin and techtochrysin induced significant (P < 0.05) adipogenesis like insulin and enhanced adipogenesis like rosiglitazone. Wogonin and norwogonin also exhibited significant (P < 0.05) glucose uptake activity. Conclusion: The present study demonstrated that the flavonoids isolated from the T. indica stems possess antidiabetic potential revealing insulin-like and insulin sensitizing effects which were significant among the compounds. This also rationalizes the traditional use of T. indica in the management of diabetes in Malaysia.